Changes in ECT services in India since the implementation of its mental health care act 2017: a clinician’s perspective - Preeti Sinha; Vanteemar S. Sreeraj; Shyam Sundar Arumugham; Jagadisha Thirthalli (BMC Psychiatry)
Abstract Background The large treatment gap in mental disorders in India also includes a lack of access to electroconvulsive therapy (ECT), a potentially lifesaving treatment. With the introduction of the Mental Health Care Act (MHCA) 2017 in India, an impact was speculated on the utilisation of ECT due to the ban on unmodified ECT and the regularisation of ECTs in children. Methods We planned this survey to identify the current status of ECT services in India as perceived by psychiatrists and to explore the barriers to providing ECT, particularly those influenced by the enactment of the MHCA 2017 in India. The psychiatrists practising in India were invited to complete an online questionnaire distributed through social media and professional group forums. A total of 225 consenting participants completed the survey. Results A majority of the participating psychiatrists (n = 160; 71.11%) were from urban areas, and 102 (45.33%) worked in private hospitals. Approximately half of the respondents (n = 118; 52.44%) could provide ECT to less than a quarter of patients for whom ECT was recommended. Furthermore, 52.4% of psychiatrists (n = 118) reported a decrease in the number of patients receiving ECT following post MHCA 2017 in India, while 44.9% (n = 101) observed no change. Additionally, 114 psychiatrists (50.67%) noted a reduction in the use of ECT for children since MHCA 2017. A substantial proportion (78.22%; n = 176) regarded patient refusal of consent as a significant factor. Access to anaesthesia services and associated costs was identified as a major barrier by 59.1% of psychiatrists (n = 133), significantly influencing their opinion on the reduction of ECT services post-MHCA 2017 (Odds ratio = 2.024, p = 0.018). Conclusions The limited availability of anaesthesia services and associated expenses are significant barriers to using ECT in developing countries such as India. This issue became more pronounced after the implementation of the MHCA 2017 and should be addressed promptly. Training psychiatrists in ECT anaesthetic skills via task-sharing and telementoring can help resolve this issue.